Can digital literacy shaped by SES-driven social capital predict secondary school graduates' access to higher education?: exploring the impact of gender - Alam, Gazi Mahabubul; Wang, Shiwei; Bashir, Karima; Lei, Miao (Elsevier, 2026)
In the discussion of social capital and social equality, gender is still one of the most important variables that may navigate once's opportunity to pursue higher education. Despite numerous studies having examined the influence of digital literacy, socioeconomic status (SES), social capital, and their subsequent impact on access to higher education (HE), investigating the inputs and output paths of graduates using gender as a theme is yet to be done. Viewing the input path as secondary education certification and admission into university as the output path, 623 secondary school graduates for Study-1 and 635 secondary school graduates for Study-2 were examined using the quantitative method. Primary data was collected through a questionnaire to assess one independent variable (social capital), while secondary data stored in the institutions serve to measure the independent (SES), mediator, moderator and dependent variables. Multiple regression, interaction terms and KHB (Karlson-Holm-Breen method) analysis were utilized to analyse the data. Results indicated that SES-driven social capital predicts the digital literacy, and digital literacy mediates the relationship between graduates' social capital and access to HE. Furthermore, gender does not moderate the correlations between digital literacy and access to higher education. This paper contributes to the discourse on technology in societies and inequalities in higher education. The study concludes that digital discrimination increases inequality in terms of people's access to higher education. However, gender does not pose any technological discrimination for graduates in China.